Disruptive risk management: what makes supply chains resilient to low probability/ high impact disruptions to the inbound and outbound aspects of the supply chain? A systematic literature review - Richardson, Delia (Cranfield University, 2006)
The business community has found itself in the predicament of first understanding and then knowing how to deal with the risk and disruptions to which it is exposed. Risk management is a well informed field in other disciplines. Supply chain risk management however, still needs to be understood and adequately practised, but seemingly, of even more urgency is disruption risk management, which as a new hot topic, is still evolving in both the academic and the practical fields. To compound the problem is the fact that not all practitioners believe that this risk actually exists and that they need to plan for it. If they believe that it exists, they still are unsure as to how to prepare for it and many still need to be convinced that money needs to be put aside to plan for and to mitigate against disruptive events. Disruptive events such as acts of nature, accidents, terrorist and non-terrorist activities can cause a breakdown in the supply chain and thus very quickly cripple the supply chain, possibly causing disruptions to the transportation, communication and information technology systems. This is indeed a critical situation given the fact that many companies have chosen efficiency over effectiveness by employing such strategies of JIT, outsourcing and single sourcing strategies (Norrman, Jansson, 2004; CLSCM 2003, Christopher 2005, Tang 2006). In effect what they have done is exposed their supply chains making them very vulnerable to disruptive events. This report then, seeks to answer what makes a resilient supply chain. To this end the author has used the systematic review process in an attempt to use evidence-based methods of scientific research (Tranfield et al., 2003) to identify, select and critically appraise relevant research. The process is so designed that the information, once discovered and developed can then be discussed and synthesized. The broad fields of literature will include Supply Chain Risk, Vulnerability, Resilience, Risk Management and Disruption Risk Management. Findings thus far indicate that resilient supply chains have seemed to evolve from business continuity planning and supply chain risk management. Additionally, they are hinged on creating a flexible and agile supply chain, having enhanced communication within the network and establishing the right company culture. Firstly, the report seeks to situate the research in the current body of knowledge. It then describes in detail the methodology employed for the research and analysis of the information. The descriptive and thematic findings are presented, followed by their synthesis, discussion and conclusion. One of the main purposes and benefits of the systematic review is that it sets the stage to allow an issue to evolve, which can then be used to frame a PhD question. To this end, the conclusion includes PhD questions that the author has found of interest and considers as good, sound and feasible for further research and analysis.